PSIKOLOGI KOMUNIKASI DALAM PENYAMPAIAN INFORMASI KESEHATAN MELALUI PERSPEKTIF PENDIDIKAN BAHASA ARAB - Fauziah Nur Panjaitan; Leoni Wilyam (Jurnal Psikotes, 2025)
Effective health communication is essential in improving people's understanding of health issues, especially in Arabic-speaking communities. This study aims to analyse the application of communication psychology in delivering health information through Arabic as well as how Arabic language education can influence the effectiveness of health communication. Using a qualitative approach, this study used literature analysis and in-depth interviews with health practitioners and Arabic language educators to explore the psychological factors that influence health communication. The study found that psychological principles of communication, such as empathy, perception management, and persuasion, were instrumental in improving audience understanding of the health messages conveyed. In addition, the values embodied in Arabic education, such as communication ethics, the use of clear and understandable language, and cultural considerations, make an important contribution in building an effective relationship between the messenger and the audience. However, challenges faced in Arabic health communication include dialectal differences, cultural barriers, and low health literacy in some communities. This study suggests the need for a more contextualised and value-based approach in Arabic language education to improve the effectiveness of health communication. The findings are expected to contribute to the development of health communication strategies that are more effective and suited to the needs of Arabic-speaking communities.